Porous Co3O4 nanoplates as the active material for rechargeable Zn-air batteries with high energy efficiency and cycling stability. (1st January 2019) - Tan, Peng; Chen, Bin; Xu, Haoran; Cai, Weizi; He, Wei; Ni, Meng
Abstract: Efficient electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are crucial for rechargeable Zn-air batteries. We report porous Co3 O4 nanoplates with the average size and thickness of ∼100 and ∼20 nm, respectively, and a surface area of 98.65 m 2  g −1 . The mesoporous nanostructure shortens the lengths for ion/electron transport and provides abundant reaction sites. In the alkaline solution, the Co3 O4 nanoplates exhibit a comparable limiting current density to that of Pt/C in the ORR and a superior activity in the OER. Redox reactions corresponding to the oxidation/reduction of cobalt species with a high pseudocapacitance and stability are observed, indicating the multifunctional properties. Using Co3 O4 nanoplates in the air electrode, the Zn-air battery delivers a maximum power density of 59.7 mW cm −2 . At a current density of 1 mA cm −2, a gravimetric energy density of 901.6 Wh kgZn −1 and an energy efficiency of 67.3% are achieved. Moreover, the voltage gaps between discharge and charge as well as the energy efficiency of 58% at 10 mA cm −2 are maintained for 100 cycles. The porous Co3 O4 nanoplate is a promising active material for efficient Zn-air batteries with excellent cycling stability and high energy density. Highlights: Porous Co3 O4 nanoplates with a small average diameter of ∼100 nm are synthesized. High oxygen reduction/evolution activity and high pseudocapacitance are exhibited. Zn-air battery delivers a gravimetric energy density of 901.6 Wh kgZn −1 . Stable voltage gaps and high energy efficiency of 58% over 100 cycles are achieved.